2012
DOI: 10.1248/bpb.b12-00228
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Efficacy of Continuous Mild Heat Stress on the Antifungal Susceptibility of <i>Candida albicans</i> Biofilm Formation

Abstract: Elevation in the temperature induces heat stress to both host cells and the invading pathogen. This study aimed to determine whether continuous mild heat stress (increased temperature without causing significant damage to host cells) can increase susceptibility of biofilm formation of the opportunistic fungal pathogen Candida albicans to low concentrations of three typical antifungal agents. In this way the side effects associated with higher concentrations of the antifungal agents on host cells would be reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The germination times were much earlier and the germination rates higher at 39 and 41°C than those at the control temperature of 37°C. This result is similar to that described by Cho et al in their study of C. albicans biofilm formation (26). We also find that polar growth (i.e., coherent directional growth) was noticeable only at 37°C.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The germination times were much earlier and the germination rates higher at 39 and 41°C than those at the control temperature of 37°C. This result is similar to that described by Cho et al in their study of C. albicans biofilm formation (26). We also find that polar growth (i.e., coherent directional growth) was noticeable only at 37°C.…”
Section: Discussionsupporting
confidence: 93%
“…Cowen and Lindquist (25) found that the susceptibility of planktonic C. albicans cells from clinical isolates to fluconazole is increased by mild heat stress. Cho (26) believes that continuous mild heat stress increases the susceptibility of C. albicans biofilm to antifungal drugs, such as fluconazole, micafungin (MCF), and amphotericin B (AMB). Given the fact that A. fumigatus differs greatly from C. albicans with regard to genotype and phenotype, leading to its superior adaptability and more favorable entry, it is reasonable to determine whether antifungal drug susceptibilities are affected by mild heat stress in this pathogenic fungus.…”
mentioning
confidence: 99%
“…This condition simulates fever symptoms in infectious diseases. In our previous report, mild heat stress induced the antifungal susceptibility of C. albicans SC5314 biofilm 9) . However, what occurred in the cells due to mild heat stress remained to be solved.…”
Section: Mild Heat Stress Extends the Period Of Hyphal Maintenance Inmentioning
confidence: 79%
“…In particular, mild heat stress at two or four degrees higher than 37ºC led to increased susceptibility of C. albicans biofilm to antifungal agents such as micafungin, fluconazole, and amphotericin B. The difference in component ratio of yeast and hyphae at an early stage of biofilm formation may be the reason for the increased susceptibility of C. albicans biofilm to antifungal agents under conditions of mild heat stress, although the difference was observed only microscopically 9) . Moreover, biofilm at over 39ºC was observed to somewhat repress further biofilm growth.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation